SecA interacts with ribosomes in order to facilitate posttranslational translocation in bacteria - Huber, Damon; Rajagopalan, Nandhakishore; Preissler, Steffen; Rocco, Mark A.; Merz, Frieder; Kramer, Günter; Bukau, Bernd (Molecular cell, 2011)
In Escherichia coli, translocation of exported proteins across the cytoplasmic membrane is dependent on the motor protein SecA and typically begins only after synthesis of the substrate has already been completed (i.e., posttranslationally). Thus, it has generally been assumed that the translocation machinery also recognizes its protein substrates posttranslationally. Here we report a specific interaction between SecA and the ribosome at a site near the polypeptide exit channel. This interaction is mediated by conserved motifs in SecA and ribosomal protein L23, and partial disruption of this interaction in vivo by introducing mutations into the genes encoding SecA or L23 affects the efficiency of translocation by the posttranslational pathway. Based on these findings, we propose that SecA could interact with its nascent substrates during translation in order to efficiently channel them into the “posttranslational” translocation pathway.